Mentha choujunensis, a new species from Indian Trans-Himalayan region of Ladakh - Ganie, Aijaz Hassan; Islam, Tajamul; Khuroo, Anzar Ahmad; Rasool, Nazima; Banoo, Sakina; Ali, Liyaqat; Reshi, Zafar A. (Phytotaxa, 2024)
Mentha choujunensis (Lamiaceae), a new species from Suru valley of district Kargil in Ladakh, Trans-Himalaya, India is described here. The new species can be distinguished from its closest congeneric M. longifolia in possessing prostate stem, leaves petiolate and ovate to ovate-lanceolate, sparsely pubescent, trichomes 1-celled on adaxial side and 2-celled on abaxial side, base oblique, margin serrate, calyx less than half the length of corolla tube, 8–10 veined, calyx teeth reddish brown with distal trichomes 3–4 celled long and corolla white. Photo-illustrations, comparison of diagnostic characters of the new species with M. longifolia and taxonomic key for the Indian species under section Mentha are provided to facilitate field identification.